A Case study on the health and safety of a selected public elementary school for in-person learning under the new normal - Bautista, Mark Dave Q. (College of Home Economics, University of the Philippines Diliman, 2021)
This study examined the health and safety of the facilities, especially the classrooms, of a selected public elementary institution in the province of Bulacan by evaluating its physical environment, identifying the underlying factors for health and safety through user experience, and analyzing its adherence to existing COVID-19 guidelines for future in-person learning in schools. This research applied a qualitative case study framework with mixed methodologies consisting of an on-site observation through a thrid-person observer and a survey questionnaire administered online. The 5 classrooms, 20 teachers, and 27 student respondents were selected purposively to obtain results from the instrumentations. The gathered data from the observation was analyzed using the supportive design theory criteria and existing guidelines on the required health standards in schools while the numerical data from the survey questionnaire were interpreted using frequency distribution. Content analysis was used to cross-examine the qualitative data from the observation and the empirical data from the questionnaire that showed congruence in the response gathered. The interpreted results suggest that the studied school was found to deliver a healthful environment for both teachers and learners through its evident adherence to existing standards for both its learning facilities and additional protocols for new normal learning. Additionally, with the variability of classroom settings, the results of the study suggest that a multi-dimensional analysis of the classroom environment involving physical environment, user experience and health and safety factors may help determine the interior design standards in public elementary school classrooms for in-person learning under the new normal.